Correlation Between Complete Blood Count Parameters and Appendix Diameter in the Diagnosis of Acute Appendicitis: A Cross-Sectional Study (Bangladesh Journal of Radiology and Imaging, 2026)
Background: Acute appendicitis is a common surgical emergency, and early diagnosis is crucial for optimal patient outcomes. Complete blood count (CBC) parameters, including white blood cell (WBC) count, neutrophil-to-lymphocyte ratio (NLR), platelet count (PLT), mean platelet volume (MPV), and C- reactive protein (CRP), are frequently used in clinical practice to assist in thediagnosis of acute appendicitis. This study aimed to evaluate the correlation between these CBC parameters and appendix diameter as measured by ultrasonography in patients with suspected acute appendicitis.Methods: A cross-sectional study was conducted with 120 patients diagnosed with acute appendicitis. The mean age of the participants was 28.4 ± 10.2 years, and 60% were male. Clinical symptoms, CBC parameters, and appendix diameter were recorded. Statistical analysis was performed to assess the correlations between CBC parameters and appendix diameter.Results: A strong positive correlation was found between WBC count, NLR, and CRP levels with appendix diameter (p < 0.001). Platelet count and MPV showed moderate correlations (p < 0.05), while platelet distribution width (PDW) and redcell distribution width (RDW) did not exhibit statistically significant correlations with appendix diameter. The mean appendix diameter in the study cohort was 7.8 ± 1.6 mm, with 70.8% of patients having an appendix diameter greater than 6 mm. Conclusion: WBC count, NLR, and CRP strongly correlate with appendix diameter and can serve as reliable biomarkers for diagnosing acute appendicitis. Platelet count and MPV may provide supplementary information, but PDW and RDW are less useful for this purpose. These findings suggest that CBC parameters can be valuable adjuncts to clinical evaluation and imaging for the diagnosis and assessment of acute appendicitis.